Hinter der Fassade. Das institutionelle System der Denkmalpflege in der DDR untersucht am Beispiel der thüringischen Städte Erfurt, Weimar und Eisenach. - Wüllner, Katja (My University, 2016)
Anhand der drei kulturgeschichtlich herausragenden thüringischen Städte - Erfurt - Weimar - Eisenach - werden die institutionellen und denkmalpolitischen Rahmenbedingungen, sowie der Stellenwert denkmalpflegerischer Bemühungen für die Kulturpolitik untersucht. Den Schwerpunkt der Betrachtungen bildet die Zeit vom Beginn der 1960er Jahre bis zum Ende der DDR. In diesen Zeitraum fallen zum einen die Gründung einer eigenen Arbeitsstelle Erfurt des Zentralen Instituts für Denkmalpflege und zum anderen die beginnende Aufwertung der Denkmalpflege in den 1970er Jahren, deren formalen Höhepunkt das im Juli 1975 verabschiedete Denkmalpflegegesetz darstellt. Über die institutionellen Rahmenbedingungen der Denkmalpflege in Erfurt, Weimar und Eisenach hinaus fragt die Arbeit nach den Handlungsspielräumen, Grenzen sowie den Spannungsfeldern.

Based on the Thuringian cities of Erfurt, Weimar and Eisenach, the doctoral thesis "Hinter der Fassade. Das institutionelle System der Denkmalpflege in der DDR" examines the institutional system in which the historic preservation in the GDR was embedded. Based on the example of the three cultural-historically outstanding cities, the institutional and monument-political framework conditions as well as the importance historic preservation attempts for cultural politics are examined. The key aspect of the observation is the time from the start of the 1960s up to the end of the GDR. On one hand, this time incorporates the establishment of an own office of the Zentrale Institut für Denkmalpflege (Institute for Historic Preservation) in Erfurt and the onset of the appreciation of historic preservation during the 1970s on the other, the formal climax of which is the Denkmalpflegegesetz (Historical Preservation Law) adopted in July 1975. Beyond the institutional framework conditions of historic preservation in Erfurt, Weimar and Eisenach, the dissertation enquires about the latitudes, limits and tension areas resulting from the various actor constellations on a local, regional and national level. The examination not only focuses on the professionalised historic preservation, but also the civil-societal commitment for monuments.
Behind the façade. The institutional system of historic preservation in the GDR exemplified by the Thuringian cities of Erfurt, Weimar and Eisenach.
Keywords: Denkmalschutz; Denkmalpflege; Historische Stadt; Kulturpolitik; Institutionengeschichte; Kulturlandschaft; Denkmalpflegegesetz; Rahmenbedingung; Handlungsspielraum; Ehrenamt; Bürgerengagement; Bürgerhaus; Repräsentativbau; Gedenkstätte; Fallbeispiel